The Chinese herbal formulae (Yitangkang) exerts an antidiabetic effect through the regulation of substance metabolism and energy metabolism in type 2 diabetic rats. (15th July 2019) - Han, Xueying; Yang, Yufeng; Metwaly, Ahmed M.; Xue, Yawei; Shi, Yan; Dou, Deqiang
Abstract: Ethnopharmacological relevance: Type 2 diabetes mellitus (T2DM) regarded as a "hot" disease in traditional Chinese medicine (TCM). Accordingly, TCM uses a cold drug or formula such as the Chinese herbal formulae "Yitangkang" (YTK) as a treatment. YTK exhibited a good clinical antidiabetic effect in several experiments. The correlation between the properties of a TCM drug or formula and its ability to regulate the substance metabolism, the energy metabolism and the endocrine system has been proven. Aim of the study: The present study aiming to evaluate the mechanism of antidiabetic action of YTK from the above perspective. Materials and methods: Three groups of streptozotocin (STZ)-diabetic rats have been treated with YTK at oral doses of 56 g/kg/d, 28 g/kg/d and 14 g/kg/d for 28 days using metformin as a reference drug. After treatment, several indices correlated with energy metabolism (superoxide dismutase, glutathione peroxidase, lactic dehydrogenase, adenotriphos, creatine phosphate kinase, AMPK, Na + -K + -ATPase and Respiratory Chain Complex I, II, III, IV), substance metabolism (hepatic glycogen, acetyl-coenzyme A, pyruvic acid, adipose triglyceride lipase, triglycerides, high-density lipoproteins, low-density lipoproteins, malonyldialdehyde), endocrine system (triiodothyronine, thyroxine, 17-hydroxycorticosteroid) and cyclic nucleotide system (cyclic adenosine monophosphate, cyclic guanosine monophosphate) have been determined. The specialty and tendency of YTK's effects were analyzed to elucidate its property and mechanism of action according to the theory of TCM. Results: Our findings showed that the formulae YTK could effectively regulate the levels of blood glucose, HbA1c, glucagon-like peptide-1, and significantly down-regulate the substance metabolism, energy metabolism and endocrine system indices of the diabetic rats. Conclusion: These results were consistent with the TCM description of YTK as a "cold" treatment. It could provide an effective way to interpret the scientific connotation and comprehensive system of the Chinese herbal formulae. Graphical abstract: Image 1